1999
DOI: 10.2135/cropsci1999.0011183x003900030037x
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographic Information to Acquire Wild Crop Germplasm for Ex Situ Collections: I. Map Development and Field Use

Abstract: A common strategy for sampling intraspecific genetic diversity is to maximize the sampling of geographically distinct populations. The objective of this study was to illustrate how geographic information coupled with geographic information systems (GIS) analysis can provide a new level of precision for establishing frameworks for sampling germplasm occurring in ecogeographically diverse sites. An exploration to collect forage germplasm in the western Caucasus Mountains in southern Russia, carried out jointly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The regression analysis revealed that between monthly mean, maximum and minimum temperature values and elevation values linear relationships were produced. These findings agreed with those of the previous studies conducted elsewhere (Phillips et al, 1992;USDA, 1998;Greene et al, 1999;Yazdanpanah, 2001;Daly, 2002;Silva and Blanco, 2003;Chuanyan et al, 2004). Estimated monthly maximum, mean and minimum temperatures were highly significant (p < 0.001).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The regression analysis revealed that between monthly mean, maximum and minimum temperature values and elevation values linear relationships were produced. These findings agreed with those of the previous studies conducted elsewhere (Phillips et al, 1992;USDA, 1998;Greene et al, 1999;Yazdanpanah, 2001;Daly, 2002;Silva and Blanco, 2003;Chuanyan et al, 2004). Estimated monthly maximum, mean and minimum temperatures were highly significant (p < 0.001).…”
Section: Resultssupporting
confidence: 91%
“…The relative humidity values decreased towards south, and the highest relative humidity values occurred in the coastal areas, depending on the temperature, and topographic characters of the region and the influence of the Black Sea (Figure 4). Accumulated rainfall values were used to create the spatial rainfall layers (Greene et al, 1999). Log transformation was used to fit the rainfall data into a normal distribution.…”
Section: Resultsmentioning
confidence: 99%
“…We considered values above 0.8 as very strong, between 0.6 and 0.8 as strong, between 0.4 and 0.6 as moderate, between 0.2 and 0.4 as weak, and between 0 and 0.2 as very weak. Greene et al (1999aGreene et al ( , 1999b demonstrated the utility of geographic information systems (GIS) analysis, combining physical distance and environmental data, in exploring sampling protocols. We tested associations of disease and pest resistances to climatic variables following our same methodologies in Jansky et al (2006Jansky et al ( , 2008.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, published maps showing a specific factor of interest to the conservationist (or combination of factors) may not be available. An example of the use of GIS to develop mapping products for use in the field is provided by Greene et al (1999a). A number of moisture and temperature maps synthesizing some 60 monthly climate variables at 500 m resolution were prepared in support of a joint USA/Russia forage collecting programme in the Caucasus.…”
Section: Field Aidsmentioning
confidence: 99%